KONTRIBUSI KOMPETENSI SUPERVISI AKADEMIK PENGAWAS TERHADAP MUTU PEMBELAJARAN DI SEKOLAH MENENGAH ATAS NEGERI KOTA CIMAHI - Muhammad Faisal (Jurnal Tata Kelola Pendidikan, 2021)
This research is entitled "Contribution of Supervisors Academic Supervision Competence to Learning Quality in State Senior High Schools of Cimahi City". The purpose of this study was to obtain an overview of the contribution of supervisors' academic supervision competencies to the quality of learning in Cimahi City State Senior High Schools. This study uses a descriptive method with a quantitative approach. The data collection technique used a questionnaire with a Likert scale. The sample of this study was 79 high school teachers from a total population of 365 teachers in the Cimahi City public high school environment. Based on the results of data processing calculated using WMS, it shows that the general trend for Academic Supervision Competence and Learning Quality is in the very good category. The Academic Supervision Competency variable got a score of 3.45 and the Learning Quality variable got a score of 3.35. The results of the data analysis show a positive and significant contribution from the Academic Supervision Competence to the Quality of Learning. The results of the determination analysis show that the influence of academic supervision competence is 34%, the remaining 42% is influenced by other factors such as organizational culture, leadership, communication, etc. It can be concluded that the research hypothesis has proven that there is a positive and significant contribution of the Academic Supervision Competence to the Quality of Learning in SMA Negeri Cimahi City.